Arterial hypertension as a risk factor for cardiovascular diseases - Simões, Marcus Vinicius; Schmidt, André (Medicina (Ribeirao Preto), 1996)
Recent epidemiologic studies confirmed the role of arterial hypertension as a major risk factor for cardiovascular disease. A brief review of the hypertension clinical hallmarks regarding its repercussion on risk determination of atherosclerotic disease is presented. Concepts about left ventricular hypertrophy as a predictor of sudden death by arrythmics mechanisms are objectively updated.